Tax Enforcement and Income Diversion: Evidence after Putin’s election in 2000 - Gómez, Juan Pedro; Mironov, Maxim (Now Publisher, 2019)
Using a direct estimate of income diversion for a large sample of Russian firms from 1999 through 2004, we show that an increase in tax enforcement after Putin’s election in 2000 is associated with a decrease in the appropriation of private rents by insiders both in firms explicitly targeted as tax evaders and among the largest firms in the sample. We interpret the latter as evidence consistent with a simultaneous spillover effect derived from the threat posed by tighter tax enforcement. This effect persists both economically and statistically in a subsample of listed companies after controlling for changes in firm-level corporate governance.
Keywords: Corporate finance; Taxation; Political corruption; 53 Ciencias Económicas; ODS 1 - Fin de la pobreza